The theory of efficient growth - Germinal G. Van (Economics and Econometrics Research Institute (EERI), 2022)
The objective of this paper is to propose an analytical framework to examine the foundations of the theory of efficient growth. The theory of efficient growth is a newly developed theory based on the principles of the neoclassical framework. It argues that an economy grows efficiently under two conditions. First, that the public and the private sectors both perform independently from each other. Second, the sum of their independent performances reaches an equilibrium. This equilibrium determines the optimum point of economic growth, and this optimal point illustrates the efficiency of economic growth.
Keywords: E62; O42; O43; R13; 330; Economic growth; mathematical economics; economic theory; macroeconomics; business cycle; fiscal policy